Categorial Semantics for Predication: Introductory Remarks - Stalmaszczyk, Piotr (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The concept of predication has always been crucial for studies in linguistics, logic, and philosophy. This short note comments on a simplified version of categorial semantics for syntactic predication. The relation of predication has been analysed from semantic, syntactic, and ontological perspectives. The categorial semantics for predication proposed below aims at integrating various approaches, and it shows affinities to semantic numeration (based on the concept of numeration introduced in contemporary minimalist program of generative grammar), and employing the functional category of predication with relevant projections.